EXPERIENCE IN DEVELOPING THE PROJECT COMPETENCE OF FUTURE ENVIRONMENT DESIGN SPECIALISTS IN HIGHER EDUCATION INSTITUTIONS OF UKRAINE AND ABROAD - Maksymov, Maksym (Professional Pedagogics, 2025)
Relevance: Within the framework of European integration, the societal value of design as a vital element of the national revival of the Ukrainian state is intensifying; shifts in urban renovation standards for spaces and city infrastructure necessitate an increasing demand for qualified environment designers who possess advanced professional competence, spatial-volumetric thinking, theoretical knowledge, and practical skills; consequently, the need to identify innovative strategies for ensuring the quality of professional training for environment design specialists in Higher Education Institutions (HEIs) arises, alongside incorporating their positive attributes to enhance the design education system in Ukraine. Purpose: The study aims to conduct a theoretical and comparative analysis of "Environment Design" educational programmes at leading HEIs in Ukraine and abroad; furthermore, based on the findings, it identifies the specificities of practical experience in developing the project competence of future environment design specialists. Methods: Theoretical analysis and synthesis were employed to investigate HEI educational programmes; a systemic-structural approach helped identify the interconnections between curricula and their educational components targeted at developing the project competence of future environment designers; finally, a comparative analysis served to distinguish specific features of professional training for these specialists in both Ukrainian and foreign HEIs, which influence their project competence development levels within the educational process. Results: Based on the analysis of educational programmes (EPs) from domestic HEIs and leading global universities, the study identifies and evaluates the characteristics of project competence development; the findings reveal that the domestic model emphasises the integration of artistic disciplines with the core "Projecting" course, whereas international programmes demonstrate a deeper implementation of project-based learning principles, sustainable design, digital tools, and communication. Conclusions: The development of project competence in future environment designers constitutes a dynamic process; a key distinction of foreign programmes is a higher degree of student engagement in authentic collaboration with industry and communities; for Ukrainian education, updating teaching and methodological resources and monitoring the development levels of students’ project competence appears highly promising.